Relaxação de spin em nanoestruturas semicondutoras 0 e 2D - Laurindo, Vanderli Junior (2023)
This thesis contains a compilation of the work developed and is divided into three main parts. The first part describes the homogeneous and inhomogeneous decoherence mechanisms of excitons in GaAs/AlGaAs quantum wells. It was demonstrated that, for low temperatures, the main decoherence mechanisms are associated to the acoustic phonon scattering and short-range interactions. Fur- thermore, the results of magneto-photoluminescence with the luminescence re- solved with circular polarization, a modulation for one of the spin components of the exciton was presented as a result of a competition between short-range in- teractions and spin-flip scattering. In the second part of this thesis, the influence of substrate orientation on spin relaxation mechanism is detailed. Firtsly, it was shown that the oscillations in the integrated intensity of the luminescence in the high magnetic field regime are due to the relaxation process through the Landau levels of the electron and hole subbands, whereby the substrate orientation has no influence on these oscillations. Furthermore, it has been shown in the present study that spin inversion occurs only for the orientation of the GaAs (311)A sur- face, which is observed both with temperature and power dependence. Finally, a theoretical framework was created in order to explain the spin inversion, with- out the need of a conjecture as previously proposed. In the third and final part, the results of the magnetic control of carrier transfer are presented for the hybrid samples composed of InAs/GaAs quantum dot - InGaAs/GaAs quantum well separeted by different GaAs spacer layer. For the thicker spacer, the photolumi- nescence emission has the same behavior as the reference ones. In comparison, for the thinner hybrid sample, an increase in the integrated QW intensity was ob- served with an increasing in magnetic field, which was attributed to a change in the coupling between QD and QW as well as a change in the carrier dynamics.